Association Between Women's Empowerment and Maternal and Child Nutrition in Kalalé District of Northern Benin. Issue 3 (September 2017) - Alaofè, Halimatou; Zhu, Min; Burney, Jennifer; Naylor, Rosamond; Douglas, Taren
Background: Evidence on effectiveness of women's empowerment (WE) to reduce undernutrition is limited in sub-Sahara Africa, and few studies incorporate multidimensional measures of WE. Objective: To examine whether a WE status, in sum and across leadership, decision-making, mobility, economic security, male involvement in housework, and nonfamily group domains, is associated with women and their children nutritional status in Kalalé district of northern Benin. Methods: Data were obtained from the 2014 Solar Market Garden baseline study: 767 paired reproductive-age women aged 15 to 49 years and children 6 to 59 months old. Exploratory principal component (cross-validate with confirmatory) factor analysis was first conducted to identify the structure of empowerment. Then, using a new survey-based index, regression analysis was conducted to examine associations between WE measures and maternal dietary diversity score (DDS) and body mass index (BMI), as well as their child's DDS, height-for-age z score (HAZ), weight-for-height z score (WHZ), and weight-for-age z score (WAZ). Results: Positive associations were observed between women's composite empowerment, leadership, maternal DDS and BMI, and female child's DDS. However, opposite signs were found between economic security and child's DDS. Mobility was positively associated with female children's WHZ and male children's HAZ and WAZ, while decision-making was correlated with male child's WHZ and female children's WAZ. Conclusions: Women's empowerment can be associated with undernutrition. Efforts to improve nutrition may benefit from empowerment initiatives that promote women's self-confidence and decision-making in Benin. However, additional qualitative and longitudinal research may enhance understanding of WE in the present area.